(untitled) (BIBECHANA, 2026)
The non-destructive, in-situ open-circuit potential mapping (OCPM) technique is used to investigate the corrosion probability conditions of rebar-embedded concretes (RECs) in urban areas of Tansen Municipality, Nepal. One hundred and three (103) REC samples of five different types are assessed in the present study. Corrosion condition of 51 building pillars (BPs), 27 reinforcement road slabs (R2Ss), 10 building roofs (BRs), 10 fencing pillars (FPs), and 5 sewage supply pipes (S2Ps) are evaluated from four surface points of each sample specimen per ASTM C876-22b standards. This assessment indicates the RECs of Tansen municipality areas are in a minimal or least corrosion risk (LCR) zone, i.e., <10% probability of corrosion. RECs with rough-cracked surfaces in high humidity show a zone of severe corrosion risk per the recorded OCP values. The REC pillars of the buildings are at a slightly higher corrosion risk than the building roof slabs. Reinforcing rebars of S2Ps and FPs are more vulnerable than BRs and R2Ss of Tansen.